Arqueology of the Transcendental Question. About Michel Foucault - Díaz Marsá, Marco (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
In the framework of a general analysis about the idea of «trascendental» in Foucault’s thought, and following an arqueological procedure, the aim will be to explain the general form of modern problematization, a form in whose framework a set of new questions could have been raised, one of them being the transcendental question, the subject of our study. We will try to show, first, the bond of necessity between the breaking of representation and the rising of the possibility of a transcendental questioning. Secondly, we will explore the transcendental area, which will be characterized, starting from a problematization of the articulation critique-metaphysics, as the transcendental field of a finite subject, as the region of critical facticity corresponding to a subject which is and, at the time, acts in a world. Finally we will present the closures of this dimension in two philosophical schematizations: the ones operating as «analytics of finitude» (anthropological schematization), and the ones as «metaphysics of the object» (reducing-objectifying layout of the transcendental question)
Keywords: arqueology; trascendental; critique; critical metaphysics; critical facticity; anthropology; analytic of finitude; metaphysics of the object